Access to Justice for Coastal Communities Affected by Reclamation Projects in Indonesia - Sisilia Gunawan Saridevi; Tajuddin Ahmad Soleh Muhammad Ehsan (JUSTISIA GLOBAL EDUKASI, 2026)
Coastal reclamation projects have become an important component of Indonesia’s infrastructure and urban development agenda. However, these projects frequently generate social, environmental, and legal challenges for coastal communities whose livelihoods depend on marine and coastal resources. This study analyzes access to justice for coastal communities affected by reclamation projects in Indonesia through a sociolegal perspective. Employing qualitative sociolegal methods, the research examines the extent to which affected communities can participate in decision-making processes and seek remedies for perceived harms. The findings reveal that access to justice is often constrained by limited legal knowledge, unequal bargaining power, procedural complexities, and restricted access to legal representation. Environmental impact assessments and public consultation mechanisms frequently fail to provide meaningful participation opportunities for local residents. As a result, communities encounter difficulties in protecting their economic interests, cultural identity, and environmental rights. The study further demonstrates that legal frameworks governing reclamation projects contain important procedural safeguards, yet their implementation remains inconsistent across different regions. Strengthening community participation, legal aid services, and transparency in development planning can significantly improve access to justice outcomes. The research argues that sociolegal approaches are necessary to understand the broader social impacts of reclamation policies beyond formal legal compliance. The study concludes that ensuring equitable access to justice requires integrating human rights principles, environmental governance, and community empowerment into coastal development policies. Such measures are essential for achieving sustainable development while safeguarding the rights and welfare of affected coastal populations.